Emerging biomarkers for early cancer detection and diagnosis: challenges, innovations, and clinical perspectives - Sameen Zafar; Amna Hafeez; Hania Shah; Iqra Mutiullah; Arslan Ali; Khushbukhat Khan; Gabriela Figueroa-González; Octavio Daniel Reyes-Hernández; Laura Itzel Quintas-Granados; Sheila I. Peña-Corona; Lashyn N. Kiyekbayeva; Monica Butnariu; et al. (European Journal of Medical Research)
Abstract Early detection and accurate cancer diagnosis are crucial for improving patient outcomes and survival rates. This review presents a comprehensive and updated synthesis of emerging biomarkers, essential for providing non-invasive, efficient, and reliable methods to identify cancer in its early stages. An extensive literature review focuses on recent studies and advancements in both traditional and emerging biomarkers, including circulating tumor DNA (ctDNA), exosomes, liquid biopsies, microRNAs (miRNAs), and immunotherapy biomarkers, which show promising potential for early cancer detection. Liquid biopsies, nanobiosensors, artificial intelligence, and next-generation sequencing (NGS) are transforming biomarker discovery and application. Key challenges include low concentration and fragmentation, as well as clearance of ctDNA, the complexity of exosome isolation, inter-patient variability in miRNA expression, and the absence of clinical standardization. We also highlight the translational barriers in low-resource settings and suggest strategies for future implementation. We also underscore the limited diagnostic accessibility in low-resource settings, emphasizing the importance of equity in future applications. Future research should prioritize overcoming current challenges, promoting multidisciplinary collaboration, and creating standardized protocols to enhance the clinical utility of this approach.